La langue bretonne entre républicanisme et cléricalisme - Malo Morvan (Lengas)
This article studies some bilingual breton-french schoolbooks in their social contexts. Rather than considering the language policies as targeting languages themselves, we first show that the debates about languages are often a pretext in conflicts about clericalism. In analysing the schoolbook's paratext, we focus on the way in which both languages, french and breton, are handled in their cohabitation, and which social uses are given to them.